Passively Q-switched erbium-doped fiber laser using coated reduced graphene oxide on arc-shaped single mode optical fiber as a saturable absorber - Ahmad, Harith; Tajdidzadeh, Mojgan; Reduan, Siti Aisyah (IOP Publishing, 2018)
A passively Q-switched erbium-doped fiber laser is demonstrated using saturable absorbers based on the evanescent light field interaction of reduced graphene oxide deposited on ground arc-shaped fiber. The Q-switched operation started at 32.42 mW with a lowest repetition rate of 34.48 kHz and a pulse width of 5.05 μs. A Q-switched pulse is obtained at different levels of pump power with corresponding repetition rates and pulse widths. From the obtained results, the repetition rate increases from 34.48 kHz to 54.10 kHz; in contrast, the pulse width decreases from 5.01 μs to 2.01 μs. The average output power and pulse energy are increased by enhancing pump power from 32.42 mW to 119.5 mW. Additionally, the fundamental frequency is maintained over time with the signal-to-noise ratio of ∼55 dB, thus indicating the Q-switched process is stable over a period of 90 min.